Research the effect of 4℃ refrigerated stored apheresis platelets based on platelet metabolomics - XIA Xiaoye; LI Xuejing; SU Aihua; HAO Xiao; YE Hongyan (Zhongguo shuxue zazhi)
[Objective] To investigate the differences in metabolomics between apheresis platelets stored at 4℃ and at 22℃ with agitation, aiming to provide a theoretical basis for the cold storage of apheresis platelets. [Methods] Samples were collected at four time points (d1, d5, d10, d15) for platelets stored at 4℃ (experimental group) and two time points (d1, d5) for platelets stored at 22℃ with agitation (control group). Liquid chromatography-tandem mass spectrometry (LC-MS/MS) technology was used to detect changes in platelet metabolome levels under different storage conditions. Platelet functional activity was assessed by thromboelastography (TEG) for maximum amplitude (MA) values and flow cytometry for CD62P activation rates. [Results] Metabolites in the glycolytic pathway, key metabolites in the tricarboxylic acid cycle (citrate, α-ketoglutarate), metabolites in the purine metabolism pathway (adenine, inosine monophosphate, guanine, etc.) and amino acid metabolites significantly decreased by d5 in the control group, whereas they remained stable in the experimental group. The content of fatty acid metabolites, such as prostaglandin G2, 13(S)-HOTrE, and linoleic acid, significantly increased in the control group. Statistically significant differences in MA values were observed between the two groups at d1 and d5 (P<0.05). However, in the experimental group, as the storage time extended, the MA values at d10 and d15 showed no significant difference compared to the control group at d5 (P>0.05). The CD62P activation rate between the two groups was statistically significant (P<0.05). Additionally, the CD62P activation rate of platelets in the 22℃ group increased rapidly from d1, while it rose gradually in the 4 ℃ group. [Conclusion] Platelets stored at 4 ℃ exhibit more stable metabolic activity and slower functional deterioration, which is beneficial for extending the effective storage period of platelets.